Students’ Perceptions and Experiences of ChatGPT-Assisted Writing in EFL Contexts: A Literature Review - Fujiono; Rudi Hartono; Sri Wahyuni (Institut Agama Islam Negeri Palopo, 2025)
English as a Foreign Language (EFL) learning is heavily impacted by the development of artificial intelligence (AI) technologies—especially ChatGPT. Reviewing 15 papers acquired using the Publish or Perish application, this paper offers a literature review with an emphasis on EFL students' impressions and experiences utilising ChatGPT as a writing tool. The findings expose different student impressions of their experiences using ChatGPT to create writing projects. Generally speaking, students view ChatGPT as a useful and versatile tool in boosting writing quality, enriching vocabulary, strengthening sentence structure, and offering instantaneous feedback supporting autonomous learning. The difficulties that surface, though, are technological reliance, a loss in critical thinking ability, plagiarism worries, poor digital literacy, and ethical standards. This paper also underlines the instructor's need to manage the use of artificial intelligence to keep the learning process ethical and meaningful. The outcomes of this study should provide the basis for developing flexible language learning plans fit for technological developments.